PRESCRIPTION AUDIT OF GENERAL OPD AT A TERTIARY CARE HOSPITAL IN WEST BENGAL: CROSS-SECTIONAL STUDY - BISWAS, ARUNAVA; PAUL, SUHRITA (International Journal of Current Pharmaceutical Research, 2026)
Objective: Rational prescription practices are essential for effective healthcare delivery, ensuring optimal therapeutic outcomes and minimizing adverse effects and healthcare costs. Prescription audits are important tools to evaluate and improve prescribing behavior, especially in public health institutions in developing countries like India. Methods: A cross-sectional observational study was conducted at the General Outpatient Department (OPD) of Barasat Government Medical College and Hospital (BGMCH), West Bengal, from December 2024 to February 2025. A total of 274 prescriptions were analyzed using the World Health Organization (WHO) core prescribing indicators. Parameters assessed included prescription completeness, drug details, use of generics, fixed-drug combinations (FDCs), antibiotics, injections, and essential drug list compliance. Results: All prescriptions included patient and prescriber identifiers. The average number of drugs per prescription was 3.39. Generic drugs were prescribed in 44.53% of prescriptions, while branded drugs appeared in 347 instances. Antibiotics constituted 11.4% of drugs, and injections 1.3%. About 65% of prescribed drugs were from the National List of Essential Medicines (NLEM) 2022. Only 31.39% of prescriptions included patient instructions, and no prescriptions were written in the local language. Conclusion: The audit revealed satisfactory practices in antibiotic use and essential medicine prescribing. However, improvements are needed in diagnosis documentation, generic prescribing, and patient communication. Regular audits, standardized templates, and prescriber training are recommended to ensure rational and patient-centered prescription practices.